Formal Methods for Model-Driven Engineering 12th International School on Formal Methods for the Design of Computer, Communication, and Software Systems, SFM 2012, Bertinoro, Italy, June 18-23, 2012. Advanced Lectures - Bernardo, Marco; Cortellessa, Vittorio; Pierantonio, Alfonso; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book presents 11 tutorial lectures by leading researchers given at the 12th edition of the International School on Formal Methods for the Design of Computer, Communication and Software Systems, SFM 2012, held in Bertinoro, Italy, in June 2012. SFM 2012 was devoted to model-driven engineering and covered several topics including modeling languages; model transformations, functional and performance modeling and analysis; and model evolution management.
Keywords: Computer science; Software engineering; Information Systems; Computer Science; Software Engineering; Software Engineering/Programming and Operating Systems; Mathematical Logic and Formal Languages; Programming Languages, Compilers, Interpreters; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems